Sound Levels And Spectra At Ikot Uduak (MCC) Timber Market, Calabar, Cross River State, Nigeria - Okoro, R.C.; Bassey D.E.; Umunnah, R.A. (European Scientific Journal, ESJ, 2016)
Acoustic and physical parameters of machines at Ikot Uduak timber market in Calabar, Cross River State, Nigeria were measured using a sound level meter and a real time frequency analyzer. The sound level meter was Mastech model MS6700. This has 30dB -130dB capability, with an accuracy of ± 1.5 dB. Real Time Audio Spectrum Analyzer, version 3.3 was used. The results showed that A-weighted sound levels with the meter at 1m away from the wood working machines were 100.5 dBA, 98.5 dBA, 98.2 dBA, 101.5 dBA and 90.5 dBA for Band saw, Table saw, Plainer, Spindle/Curving machine and the Drilling machine respectively. From this, the threshold for dangerous levels of noise, as stipulated by the Academy of Pediatrics and the National Campaign for Hearing and Health, which is 85 dB., and the Occupational Safety and Health Act (OSHA) permissible level of 90dBA for 8-hour day and 5 days a week, have been exceeded, and this could lead to hearing impairments.